UTILIZATION OF WATERMARKING TECHNIQUE AS DIGITAL FINGERPRINT (DIGITAL SIGNATURE) IN DIGITAL DOCUMENT THESIS - Murwantini, Sri; Patrisia, Yulin (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2013)
The rapid development of information technology have a positive and negative impacts. In this case, the advantage with the advancement of information technology can be utilized to store a variety of undergraduate thesis work of students, especially in the Department of Vocational and Technology Education Unpar stored in digital form. By way of this paperless storage can save space and storage space. But on the other hand, it is easy to be copied by the less responsible student. One way to protect the authenticity of ownership of digital data is by using watermarking. Watermarking technique is the process of adding a permanent identification code into digital data. In this study , the focus was on how to make use of watermarking techniques in digital documents. Experiments conducted concluded that the use of space for storing watermark bits is very promising. Decoding or watermark embedding is done by inserting a watermark on each bit contained in the document space, while the watermark retrieval or decoding by taking every bit watermark of spaces contained in documents that have been inserted watermark.